Kajian Efisiensi dan Efektifitas Jaringan Jalan Daerah Jawa Barat yang Berbatasan dengan DKI Jakarta - Hadi Supratikta (Jurnal Bina Praja: Journal of Home Affairs Governance, 2014)
The road is one of the major public infrastructure to support mobilization of people and goods. Based on land transportation objectives, studies of the road performance are needed by considering various aspects such as accessibility, road safety operation, efficiency, effectiveness, affordable costs, and the integration with other transportation network system. Performance of the road network can be measured through efficiency and effectiveness parameter. Studies about the level of efficiency and effectiveness of road network systems are needed to get the real picture about the performance of the road network. The results of studies can be used as the guidance and evidence in policy making. The purpose of this study is to get the level of efficiency and effectiveness of the road network system in West Java Province, which borders with Capital City Jakarta. Methods used in this study are literature studies, collecting secondary data and related regulations, development of performance indicators, survey interviews and descriptive statistical methods to obtain a description about the interests of parties' perception and the analysis of the efficiency and effectiveness of road network in West Java Province. Based on the conclusion, the study recommend a need of comprehensive policies including input policies, ouput policies, policy objectives and policy impacts.